A Juridical Review of Constitutional Court Decision No. 18/PUU-V/2007 on the Establishment of Ad Hoc Human Rights Courts in Indonesia - Saleha, Dwi; Firmanto, Fakhry; Kusumo, Indra Suryo; Kholis, Mohammad Nur (Eastasouth Institute, 2025)
This study provides a normative legal analysis of handling defaults in Sharia mortgage (KPR Syariah) contracts based on Fatwa DSN-MUI No. 17/DSN-MUI/IX/2000 concerning sanctions for customers who are able to pay but delay payment (ta’wil). The research aims to examine the conformity of Sharia-based mortgage default handling with Islamic legal principles and Indonesian national law. Using a normative juridical approach, this study analyzes primary legal materials including the DSN-MUI Fatwa, the Compilation of Sharia Economic Law (KHES), the Law on Sharia Banking, and Financial Services Authority (OJK) regulations. The findings indicate that default handling in Sharia mortgages should emphasize fairness, compassion, and the avoidance of riba (interest), while administrative sanctions can be applied to encourage payment discipline. The study also identifies the need for synchronization between DSN-MUI fatwas and national banking regulations to ensure both Sharia compliance and legal certainty. The results contribute to understanding the practical and doctrinal implications of Islamic financial law in Indonesia’s mortgage sector.